Redes de articulación e integración en la formación docente sobre la temática: medio ambiente y salud. Córdoba, Argentina - Pierotto, Marcelo; Lucchese, Marcela; Francettic, Mónica; Rocha, Edith; Castillo, Jimena (Visión Antataura, 2018)
.